Box-type substation with adjustable ventilation structure - LU SHUANGJIA; WANG JUNXING; LIN XIANNA; LIN XIANHE; XU DONG; BAO XIAOYING; ZHOU YONGLIN; BAO ZHEYING (2022)
The utility model discloses a box-type substation with an adjustable ventilation structure, which comprises a box body, a ventilation frame is arranged on the side surface of the box body, a plurality of adjusting grooves are arranged on the side surface of the box body in the ventilation frame, ventilation holes are arranged in the adjusting grooves, the adjusting grooves are hinged with first adjusting plates, and the first adjusting plates are hinged with second adjusting plates. A driving motor is connected to the first adjusting plate, a second adjusting plate is hinged to the first adjusting plate, the second adjusting plate is rotatably and slidably connected to the side wall of the ventilation hole, the opening degree of the ventilation hole is adjusted through the first adjusting plate and the second adjusting plate, ventilation adjustment is achieved, and the heat dissipation effect of the box body is improved. 本实用新型公开了一种具有调节型通风结构的箱式变电站，包括箱体，所述箱体的侧面上设置有通风框，所述通风框内的箱体侧面上设置有若干调节槽，所述调节槽内设置有通风孔，所述调节槽铰接有第